The Impact of Promotional Activities, Product Assessments, and Paylater Features on Product Purchase Decisions on Shopee - Agus Santoso; Hartini Hartini; Nurasia Nurasia (Komunitas Dosen Indonesia, 2024)
This study aims to explain the effect of promotional activities, product assessment, and paylater features on product purchasing decisions at shopee. The study was conducted on students in Sumbawa Besar with a sample of 100 respondents who were determined using purposive sampling. Data were collected through questionnaires and analyzed using the partial least square (PLS) technique. The results of this study have shown that promotional activities have a positive and significant effect on product purchasing decisions at shopee. Product assessment has a positive and significant effect on product purchasing decisions at shopee. The paylater feature has a positive and significant effect on product purchasing decisions at shopee